Caffeine modulates Ca2+ receptor activation in isolated rat osteoclasts and induces intracellular Ca2+ release. - Shankar, V; Pazianas, M; Huang, C; Simon, B; Adebanjo, O; Zaidi, M (1995)
A ryanodine-sensitive pathway is involved in intracellular Ca2+ release in response to activation of the osteoclast cell surface Ca2+ receptor. We now report that the ryanodine-receptor modulator, caffeine itself released intracellularly stored Ca2+ and, strongly inhibited Ca2+ release triggered in response to Ca(2+)-receptor activation by Ni2+, a surrogate cation agonist. Caffeine yielded a bell-shaped concentration-response curve (0.005-2 mM) and displayed use-dependent inactivation. Furthermore, responses to caffeine were abolished on prior application of Ni2+ (5 mM). Subthreshold (0.005 mM) caffeine concentrations abolished Ni(2+)-induced elevations in the cytosolic Ca2+ concentration ([Ca2+]). However, in a Ca(2+)-free, ethylene glycol-bis(beta-aminoethyl ether)-N,N,N',N'-tetraacetic acid-containing solution (extracellular [Ca2+] < 10 nM), caffeine (0.5 mM) neither elevated [Ca2+] nor inhibited the response to Ni2+. Finally, when caffeine was applied to intercept the plateau phase of the cytosolic Ca2+ signal triggered by extracellular Ca2+ elevation (10 mM), a rapid but reversible inactivation followed. These studies strongly indicate the existence of a caffeine-sensitive mechanism for the release of intracellularly stored Ca2+ in the osteoclast.